Dual use of Altman financial failure prediction analysis and stress tests to achieve integration in banking risk management : Analytical study of the National Bank of Iraq (Journal of Accounting and Financial Studies ( JAFS ), 2022)
The research aims to demonstrate the dual use of analysis to predict financial failure according to the Altman model and stress tests to achieve integration in banking risk management. On the bank’s ability to withstand crises, especially in light of its low rating according to the Altman model, and the possibility of its failure in the future, thus proving or denying the research hypothesis, the research reached a set of conclusions, the most important of which (the bank, according to the Altman model, is threatened with failure in the near future, as it is located within the red zone according to the model’s description, and will incur losses if it is exposed to crises in the future according to the analysis of stress tests), and the research reached a set of recommendations, the most important of which are (The dual use of the Altman model and stress tests help give bank management a clear idea of ​​the real risks to implement effective and rapid reforms).